Literature and Medicine: Aspects of Connection - Abdul Jabbar, Zaynab; Abdulaali, Wafaa (Al-Adab Journal, 2024)
This article investigates the affinities of literature and medicine, projecting some of the most significant aspects where these disciplines intersect: therapy, empathy and epistemology. Literature has been used for therapy since the ancient times of Aristotle and his Theory of Catharsis. Nowadays, terms such as bibliotherapy and scriptotherapy have emerged as “reading” and “writing” are used for therapeutic purposes. Literature courses are also taught at medical colleges since the early 1980s in advanced countries, as research has proved the positive impact of such courses on healthcare workers. Pioneers of "narrative medicine" have found an analogy between medical diagnosis and the narrative elements of literature. Besides, some of the writings of patients and doctors can lead to a better understanding of disease. Physician-writers are some of the best examples where literature and medicine combine. Among the issues discussed in this exploratory article is the significance of such writings in the context of medical humanities. The research aims at drawing the attention of researchers to the field of medical humanities which has proved the importance of literature and its employment in scientific fields such as medicine. Literature is larger, benefits and significance, than to be merely the curricula at the academic departments of the humanities.